Iron and steel Institute of the NAS. Scientific and technical support of black metallurgy - Babachenko, A.I.; Tuboltsev, L.G. (Фундаментальные и прикладные проблемы черной металлургии, 2017)
The state of black metallurgy as a basic branch of the Ukrainian economy is shown. The main scientific developments of the Institute on scientific and technical support and modernization of blast furnace, steelmaking and rolling production are presented. Показано состояние черной металлургии как базовой отрасли экономики Украины. Приведены основные научные разработки Института по научно-техническому сопровождению и модернизации доменного, сталеплавильного и прокатного производства. Показано стан чорної металургії як базової галузі економіки України. Наведено основні наукові розробки Інституту з науково-технічного супроводу та модернізації доменного, сталеплавильного і прокатного виробництв.